2012
DOI: 10.1159/000338695
|View full text |Cite
|
Sign up to set email alerts
|

Functional Neuroimaging in Craniopharyngioma: A Useful Tool to Better Understand Hypothalamic Obesity?

Abstract: Objective: To use functional magnetic resonance imaging (fMRI) in craniopharyngioma (CP) patients to examine the hypothesis that hypothalamic damage due to CP and its treatment results in enhanced perception of food reward and/or impaired central satiety processing. Methods: Pre- and post-meal responses to visual food cues in brain regions of interest (ROI; bilateral nucleus accumbens, bilateral insula, and medial orbitofrontal cortex) were assessed in 4 CP patients versus 4 age- and weight-matched controls. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 62 publications
3
20
0
Order By: Relevance
“…Before and after the scans, hunger ratings were performed. Following the test meal, controls showed suppression of activation in ROIs while CP patients showed trends toward higher activation in ROIs (Roth et al, 2011a). These preliminary data support our hypothesis that perception of food cues may be altered in HO, especially after eating.…”
Section: Hypothalamic Obesity: Results From Studies In Humansmentioning
confidence: 99%
“…Before and after the scans, hunger ratings were performed. Following the test meal, controls showed suppression of activation in ROIs while CP patients showed trends toward higher activation in ROIs (Roth et al, 2011a). These preliminary data support our hypothesis that perception of food cues may be altered in HO, especially after eating.…”
Section: Hypothalamic Obesity: Results From Studies In Humansmentioning
confidence: 99%
“…Early reports of hyperphagia in CP patients led to a reluctance to consider bariatric surgery in this cohort; more recent studies have suggested that excessive calorie consumption in CP may be more subtle in aetiology—for example there may be a relative calorie excess in a state of low physical activity or there may be a selection of high‐calorie “reward” foods . Bariatric surgery therefore may be a viable tool to reduce the burden of HO in CP patients and can result in 10%‐20% weight loss at a year post‐surgery.…”
Section: Obesitymentioning
confidence: 96%
“…Functional magnetic resonance imaging (fMRI) is a powerful tool for observing the human brain’s in vivo responses to stimuli. One recent study tested satiety responses in a small group of four adolescent CP patients versus four BMI matched adolescent controls [ 79 ]. Following a test meal, controls showed suppression of activation by images of high-calorie, energy dense food while CP patients showed trends towards higher activation in regions of interest including the insula, nucleus accumbens, and medial orbitofrontal cortex.…”
Section: Clinical Manifestations and Risk Factorsmentioning
confidence: 99%